Awareness improvement amongst end users towards the economic sustainability in green homes : a research proposal / Nor Suzila Lop ... [et al.] - Lop, Nor Suzila; Zainal Abidin, Zaiwannizar; Md Zain, Noraini; Mohd Kamar, Izatul Farrita; Mat Salleh, Norazlin; Mohamad Hamdan, Noor Aishah (2012)
In recent years, people are more concerned about the environment since they know what the effects of pollution to the environment to human health would be, hence the emergence of the green home concept. This is a new concept whereby a home is created to use less energy, water and natural resources to provide good air quality and comfort to its occupants. It generates less wastage and therefore can be considered as sustainable developments that improve homeowner’s lifestyle. The Malaysian government has been encouraging the development of green homes since year 2006. In the <inth Malaysia Plan, the government has started to emphasis on sustainable development and in 2009, a new policy called the <ational Green Technology Policy has been introduced. This policy promotes the usage of green technology in developments which includes green homes. Green home can help to preserve the environment since they use renewable energy as their power source by allowing natural lighting through windows and openings. This research proposes to look into the level of perception and awareness of end users towards the economic and sustainability aspect in green home design. The objective of this research is to discover the awareness of end users as regards to sustainability in green home designs, to identify end users’ requirements in green homes and to develop a comprehensive checklist of end users’ requirements to be followed by developers. The data for this research will be collected via questionnaires and interviews which will be distributed to end users within Peninsular Malaysia. Descriptive statistics will be used to analyse the data. The findings of this research will be in the form of a comprehensive checklist as to what is required by green home end users.